Global economic and sustainability trends in green packaging: A systematic literature review - Angela, Thalia; Rusmanto, Toto (Edelweiss Applied Science and Technology, 2025)
Green packaging is increasingly recognized as a vital pathway for reconciling environmental sustainability with economic development on a global scale. This study aims to synthesize recent research trends and identify knowledge gaps to better understand the drivers, barriers, and future directions of green packaging adoption. A systematic literature review was conducted using the PRISMA 2020 methodology to analyze 40 high-quality articles selected from quartile-one journals indexed in Scopus and Google Scholar between 2019 and 2024. In line with global economic and sustainability trends, the findings reveal that rising consumer awareness, regulatory support, and material innovations drive the adoption of green packaging, enhance business performance, and advance sustainability through waste reduction and circular economy practices. However, there are still significant challenges concerning high costs, lack of technology and infrastructure, consumer behavior, and regulatory issues. To enable the rapid expansion of sustainable packaging worldwide, strategies must integrate policy, innovation, and education. This review thus offers a systematic analytical perspective and suggests that future studies should focus on sector-specific analysis, economic viability, consumer willingness, and digital technology usage in the implementation of green packaging. Analyzing these research areas from different approaches is expected to improve sustainable business models and help achieve the Sustainable Development Goals.